Lysosomal autophagy promotes recovery in rats with acute knee injury through TFEB mediation - Qingquan Xia; Xuhua Wu; Ke Rong; Zhenyu Zhou; Xujun Li; Teng Fei; Xiaofan Yin (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background To study the role of lysosomal decomposition and elimination of old bone matrix, as well as the mechanism of promoting chondrocyte growth and bone recovery through the perspective of TFEB-mediated lysosomal autophagy. Methods Rat models of acute knee injury were designed, and autophagy flow was detected by injection of autophagy inhibitors 3-methyladenine. Autophagy flow was detected by RFP-GFP-LC3 double fluorescence molecule. The expression of TFEB, DRAM, MAPLC3, and MITF were analyzed by Western blot, and the expression of genes NITF, Bcl2, and TYR in rat cartilage tissues were detected by RT-PCR. Results The number of autophagosomes was increasing in the auto group compared with the inhibitor-auto group and normal group. There was a significant difference of LC3 levels in the auto group and inhibitor-auto group compared with the normal control. The expression of TFEB, DRAM, MAPLC3, and MITF proteins by Western blot analysis were significantly increased in the auto group and decreased in the inhibitor-auto group. The expression of NITF, Bcl2, and TYR by RT-PCR determination were higher in the auto group and inhibitor-auto group than the normal group. Conclusions Autophagy can inhibit apoptosis, promote chondrocyte growth and bone regeneration, and restore knee joint injury of rats. The main mechanism is to promote the effect of TFEB-mediated lysosomal autophagy.